Penguatan Literasi Melalui Pementasan Gendang Beleq, Kelentang, dan Wayang Kulit di Desa Pesanggrahan, Lombok Timur - Meri Suryana; Suriana Pati; Lidya Sari; Yolanda Elfa Walaya; Baiq Erliyana; Qodri Mursyidi (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2026)
Cultural performances represent one of the strategic efforts to preserve and introduce cultural heritage to the community, particularly to the younger generation. Pesanggrahan Village, located in Montong Gading Subdistrict, East Lombok Regency, is known as an area that still maintains and preserves several traditional arts, including Gendang Beleq, Kelentang, and Wayang Kulit. This article is written with the aim of describing in detail the implementation of cultural performances in Pesanggrahan Village and elaborating on the benefits derived from these activities for the preservation of local culture. The writing of this article was conducted using observation, interview, and documentation methods throughout the course of the activities. These three methods were employed in an integrated manner to obtain accurate and comprehensive data regarding the execution of the performances and the community's response to the activities. The results of the observation indicate that the cultural performances in Pesanggrahan Village received high enthusiasm from various segments of the community. Community involvement was strongly evident, ranging from local artists who served as the main performers, to youth groups, and community leaders who provided support and participation. Through direct involvement in the performances, young people gain hands-on experience and a deeper understanding of their cultural heritage. It is hoped that the cultural performances in Pesanggrahan Village can continue to be held on a sustainable basis as a form of cultural preservation, while also serving as an attraction that can introduce the village's potential and cultural wealth to a broader audience, both within and outside the region.